2017
DOI: 10.4103/ijmpo.ijmpo_167_16
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal cell lymphoma: Case report, diagnosis, and management

Abstract: The symptoms of primary renal lymphoma (PRL) may mimic a renal cell carcinoma. Since the diagnosis is mostly after a radical nephrectomy, we recommend a percutaneous biopsy or cytology from the renal mass in patients who have features suggestive of a lymphoma. A magnetic resonance imaging may give an image more specific for a lymphoma. There are no clinical trials for the treatment of PRL, but all previously published case reports used R-CHOP and a few patients did better than the median survival of 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…[ 2 , 12 ] According to previous case reports, flank pain is the most common symptom in patients with PRL, which is also the main symptom of our patient. [ 3 ] Furthermore, PRL usually has aggressive B cell histopathological characteristics, [ 13 ] and since the most common pathology is DLBCL, [ 14 , 15 ] adrenal glands could also be affected, [ 16 , 17 ] which are all consistent with our case.…”
Section: Discussionsupporting
confidence: 85%
“…[ 2 , 12 ] According to previous case reports, flank pain is the most common symptom in patients with PRL, which is also the main symptom of our patient. [ 3 ] Furthermore, PRL usually has aggressive B cell histopathological characteristics, [ 13 ] and since the most common pathology is DLBCL, [ 14 , 15 ] adrenal glands could also be affected, [ 16 , 17 ] which are all consistent with our case.…”
Section: Discussionsupporting
confidence: 85%
“…Due to the low incidence of PRNHL, randomized controlled trials (RCT) have not been developed to evaluate the best treatment option, 60 however overall the therapeutic regimen for PRNHL depends on the type of lymphoma (according to the tissue diagnosis and immunohistochemistry results) which is most commonly B cell (diffuse large B cell type). 2 …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, 83 cases of primary NHL of the kidney have been reported in the English literature so far. 3 69 Herein we will review all the primary renal NHL (PRNHL) reported in the English literature and will report all the clinicopathologic findings in the published cases.…”
Section: Introductionmentioning
confidence: 99%
“…We thoroughly reviewed all 54 cases of PRL reported in the literature since 2002 (Table 1). 4,749 DLBCL was found to be the most common pathological type, and more male than female patients (64.8%) were reported. Additionally, PRL was generally located in the bilateral kidneys in younger patients (<30 years old) and in a unilateral kidney in older patients, indicating that the site of PRL is age-related.…”
Section: Discussionmentioning
confidence: 99%